Sediment Transport in Coastal Waters - Ouillon, Sylvain (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
The interface of 440,000 km long coastline in the world is subject to global change, with an increasing human pressure (land use, buildings, sand mining, dredging) and increasing population. Improving our knowledge on involved mechanisms and sediment transport processes, monitoring the evolution of sedimentary stocks and anticipating changes in littoral and coastal zones is essential for this purpose. The special issue of Water on “Sediment transport in coastal waters” gathers thirteen papers which introduce the current revolution in the scientific research related to coastal and littoral hydrosedimentary dynamics, and reflect the diversity of concerns on which research in coastal sediment transport is based, and current trends — topics and preferred methods — to address them.